Recensiones - X. X.; I. M. B.; F. V. I.; S. S.; S. M. A.; J. M. G.; S. A. (ECA: Estudios Centroamericanos, 1973)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 28, No. 293-294, 1973: 209-220.